Teachers’ Strategies to Foster Students’ Creative Thinking Skills in Biology Learning: A Systematic Literature Review - Prasetyo, Opik; Ruwaida, Ulya; Aurora, Zevira Fansisca; Oktaviana, Rina; Fajeriadi, Heri; Aulia, Nurul; Rachman, Hening Triandika (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
Teachers play a pivotal role in designing innovative biology learning strategies that cultivate students' creative thinking, a core 21st century skill. This ability is essential for generating novel ideas, solving complex problems, and making interdisciplinary connections. By integrating real world scenarios and inquiry based approaches, teachers can further enhance students’ engagement and creative capacity. This study aims to conduct a systematic literature review to identify and analyze the pedagogical strategies employed by teachers to foster students' creative thinking skills in the context of biology learning. Employing the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) methods, a comprehensive literature search was executed using the Google scholar and Scopus database, with a publication scope from 2016 to 2025. The keywords used were (